2019
DOI: 10.1111/hel.12646
|View full text |Cite
|
Sign up to set email alerts
|

Online registry for nationwide database of Helicobacter pylori eradication in Korea: Correlation of antibiotic use density with eradication success

Abstract: Background The Helicobacter pylori eradication rate has decreased with increasing antibiotic resistance. We conducted a prospective, nationwide, multicenter registry study to monitor the real status of H. pylori eradication therapy and to investigate the association between eradication success and antibiotic use density in Korea. Materials and Methods We enrolled 9318 patients undergoing H. pylori eradication therapy from 37 hospitals through “on‐line database registry” from October 2010 to July 2015. Demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
4
16
0
2
Order By: Relevance
“…In this study, a significant trend of decreasing eradication rates was observed with increasing age, which is consistent with previous reports[ 27 , 28 ]. Possible reasons include lower tolerance to and compliance with therapy, more potential complications, increased risks of drug side effects, and increased antibiotic resistance because of higher accumulated antibiotic consumption[ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, a significant trend of decreasing eradication rates was observed with increasing age, which is consistent with previous reports[ 27 , 28 ]. Possible reasons include lower tolerance to and compliance with therapy, more potential complications, increased risks of drug side effects, and increased antibiotic resistance because of higher accumulated antibiotic consumption[ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Standard triple therapy (STT) consisting of a PPI, AMO and CLA is no longer effective in many regions of the world owing to increasing CLA resistance of H. pylori ; four-drug combination therapy such as bismuth-containing quadruple therapy (BQT) or concomitant quadruple therapy (CQT) are currently recommended as first-line treatments in areas with high CLA resistance 6–8. In previous studies, the eradication rates ranged 55%–72% for STT in 7 days,16–18 80%–95% for BQT16 19–22 and 81%–90% for CQT17 23–26 as first-line H. pylori eradication treatments. The eradication rates of VA-dual and VAC-triple therapies in this study were higher than those previously reported for the 7-day STT and as high as the ones reported for BQT and CQT although the CLA resistance rate was 25% in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, STT has been recommended as the first-line therapy since the H. pylori management guidelines were first reported in 1998 [ 3 – 5 ]. A study using a nationwide online registry of H. pylori eradication reported that STT was the most common first-line therapy prescribed (91.8%) in Korea from 2010 to 2015 [ 6 ]. However, because of the increased clarithromycin resistance (17.8%-45.9%) [ 7 , 8 ], two meta-analyses including the studies reported from 1998 to 2013 and a nationwide multicenter randomized study reported in 2019 showed that the eradication rates of STT have decreased to unacceptable levels (63.9–74.6%) in Korea [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The European and North American guidelines also recommended the BQT as an empiric first-line therapy in high clarithromycin resistant regions [ 1 , 2 ]. However, in the nationwide registry database, the prescription rate of BQT as first-line therapy in Korea was low (2.2%) [ 6 ]. The low prescription rate of the regimen as first-line therapy is related to the fact that the regimen is reserved for a second-line therapy after the first-line STT failure [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation